MVP [videorecording (DVD)] - Boyer, Nate; Boyer, Nate; Mo (Mo McRae); Gonzalez, Tony, 1976-; Shihabi, Dina; Arnold, Tom, 1959-; Glazer, Jay (FilmRise, 2023)
On the streets of Hollywood, a retired NFL player is saved from scandal by a homeless veteran suffering from PTSD. With their glory days behind them, the two men bond in search of true purpose and identity. Inspired by true events, it dramatizes the formation of Merging Vets & Players, and the film features veterans and former professional athletes both in front of and behind the camera.